Black Holes and Cosmology: Linking Physics, Philosophy, and Theology - Carr, Bernard (Zygon, 2025)
The boundary between physics and philosophy is often blurred at the frontiers of knowledge because the ideas involved are not initially testable. Interesting examples of this arise in the context of cosmology and black holes, with the nature of time and singularities - also topics on the physics/philosophy interface - providing an important link between these areas of research. The history of cosmology and black holes also connects physics and theology, pioneering papers on both topics having been written by priests. Some questions addressed by cosmologists clearly have religious implications and - although the theological aspects of black holes are less clear - the physics of black holes and cosmology are closely related.